Advantages and Disadvantages of Electric Vehicles and Hybrid Electric Vehicles (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article explores the advantages and disadvantages of Electric Vehicles (EVs) and Plug-in Hybrid Electric Vehicles (PHEVs) as transformative solutions in the automotive industry. The analysis covers key aspects, including environmental impact, energy efficiency, operating costs, and technological innovation. While EVs and PHEVs offer zero-emission benefits and reduced reliance on fossil fuels, challenges such as limited range, charging infrastructure, and upfront costs are discussed. The conclusion emphasizes the pivotal role these vehicles play in sustainable transportation, underscoring the need for ongoing technological advancements and infrastructure development to fully unlock their potential. As the automotive landscape evolves, understanding the nuanced dynamics of EVs and PHEVs becomes essential for informed decision-making and fostering a cleaner, more sustainable future.